RESISTANCE OF SOME IRANIAN HARDWOODS AGAINST MARINE BORERS IN BOSHEHR PORT COAST (PERSIAN GULF) - Ali Reza nezhad (Regional Information Center for Science and Technology (RICeST), 2004)
Four hardwood species including: Alder (Alnus subcordata), Oriental plane (Platanus orientalis), Eucalyptus camaldulensis and Babul (Acacia arabica) were treated with Creosote and Celcure. The dimension of samples was 20 x 7.5 x 2 cm. Both preservative treated and untreated samples were placed in seawater (Boshehr in Persian Gulf) according to IRG/WP-4432 (1985). After 9, 15, 24, 29, 38, 47, 53, 58 and 64 months, the samples were inspected according with recommendation of IRG/WP-4432(1985) and ASTM D- 240. All the control samples (untreated wood) of Alder and Oriental plane over 9 months, Eucalyptus and Babul over 20 months, were seriously attacked. Treated samples with Celcure of Alder and Oriental plane after 38 months were completely damaged and Eucalyptus over 38 months were severely degraded. Creosote treated samples of Eucalyptus over 58 months and Babul over 38 months were seriously attacked. Creosote treated of Alder and Oriental plane samples after 64 months installation were sound. It can be concluded that treatment with Creosote using full cell process (Bethel) increased resistance of investigated wood species against marine borers.